The Influence of E-WOM, Brand Awareness, and Brand Image on Z-Generation Purchasing Decisions on Compass Sneakers in Indonesia - Lestari, Elisa Jayanti (Journal of Management Studies and Development, 2024)
This study aims to determine the direct effect of Electronic word of mouth (E-WOM) brand awareness and brand image on purchasing decisions. One company that utilizes the development of the internet in terms of E-WOM is Compass Shoes. Compass shoes are increasingly recognized and trusted by the archipelago as a must-have fashion shoe. With its current status, not a few and even more people from various circles are interested in having these shoes. The data in this study were obtained from an online survey of 100 respondents.  In practice, this study uses accidental sampling techniques that will be applied to respondents via Google form using the type of SEM analysis used in this study, which is Partial Least Square or PLS-SEM.  The result of this study states that E-WOM has a significant positive effect on brand image and consumer purchasing decisions regarding Compass shoe products. Brand awareness has a significant positive effect on brand image and consumer purchasing decisions regarding Compass shoe products. Brand image has a significant positive effect on consumer purchasing decisions regarding Compass shoe products. Companies are important in utilizing E-WOM and building brand awareness and a strong brand image.